Sustainability of the remaining agricultural Commons in the Brazilian Northeast: challenges beyond management - Ferraro Júnior, Luiz Antonio; Bursztyn, Marcel; Drummond, José Augusto (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Abstract This article examines fundos de pasto (FPs) – a land use system that combines individual and collective appropriation of resources, evaluating its prospects in a rapidly modernizing economy. FPs are ancient and commonly held agricultural and animal husbandry lands located in the Brazilian Northeast Region. Aggressive land grabbing practices in the 1970s and 1980s and resistance of FP communities led to the formal acknowledgment of FPs. Data were obtained via individual interviews, workshops with stakeholders, archival materials from government agencies, and secondary studies. Our findings reinforce the perception of sustainability and higher resistance of these communities in years of severe droughts. Despite their secular sustainability, FPs have been under pressure that may lead to overgrazing, such as reduced grazing areas (on account of land grabbing), population growth, larger herds credit operations that stimulate the substitution of native grazing vegetation, and increasingly serious droughts. Our findings also indicate the existence of tensions between economic development and the sustainability of common resource use systems associated with the conservation of extensive areas. Understanding these tensions requires attention to the dimension of farmers’ political organization, a perspective that goes beyond the measurement of social capital.